Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1093/beheco/arr165
|View full text |Cite
|
Sign up to set email alerts
|

Honey bees use social information in waggle dances more fully when foraging errors are more costly

Abstract: Social animals can obtain valuable information from group members, but sometimes experience conflicts between this social information and personal information obtained through their own experience. Experienced honey bee foragers (Apis mellifera) have personal information about familiar food sources, and can also obtain social information by following waggle dances. However, it is unclear whether temporarily unemployed foragers whose visits to a food source have been interrupted make full use of social informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 30 publications
0
35
0
1
Order By: Relevance
“…Our findings help to explain the puzzling observation that experienced foragers following dances frequently ignore spatial waggle dance information [29], [69][74]. Our results show that foragers should continue to visit familiar food sources if these remain profitable in order to avoid recruitment costs and the lower benefits of individual exploration [23], [24], [60].…”
Section: Discussionmentioning
confidence: 63%
“…Our findings help to explain the puzzling observation that experienced foragers following dances frequently ignore spatial waggle dance information [29], [69][74]. Our results show that foragers should continue to visit familiar food sources if these remain profitable in order to avoid recruitment costs and the lower benefits of individual exploration [23], [24], [60].…”
Section: Discussionmentioning
confidence: 63%
“…Sticklebacks (Pungitius pungitius), for example, use individual learning to make foraging decisions when competition is high, but rely almost entirely on social learning when competition is low [36]. Honeybees (Apis mellifera) rely heavily on social information when foraging resources are unevenly distributed and are more likely to use individual information when resources are evenly distributed [20]. Foraging returns for rats (Rattus norvegicus) are likely to be highly variable because some potential food items are harmful or fatal, and rats exhibit strong preferences for socially learned food items [37].…”
Section: Discussionmentioning
confidence: 99%
“…Previous models have shown that the fitness of learning strategies is frequency-dependent [6]. Although these models generate the mixed-learning strategies seen in nature, there is little empirical evidence for either the costs or low fidelity of social learning when compared with individual learning [20][21][22]. Thus, the wide use of individual learning in nature remains poorly explained.…”
Section: Introductionmentioning
confidence: 99%
“…We sampled the most active followers among many followers attending to a dancer. This method might have helped us to avoid sampling bees that would ignore dance information because bees that have followed waggle runs many times (and so appear to be especially active in dance following) tend to use dance information (Wray et al 2011).…”
Section: Discussionmentioning
confidence: 99%